Early Intervention with Parents of Children with Autism Spectrum Disorders: A Review of Programs - Liliana Paulina Rojas-Torres; Yurena Alonso-Esteban; Francisco Alcantud-Marín (MDPI AG, 2020)
The aim of this article was to analyze the evidence regarding the effectiveness of intervention programs for children with autism based on the participation of their parents. To obtain the data, a systematic search was carried out in four databases (PsycARTICLES (ProQuest), ERIC (ProQuest), PubMed (ProQuest), and Scopus). The retrieved documents were refined under the inclusion/exclusion criteria, and a total of 51 empirical studies were selected. These studies were first classified according to the function of the intervention objective and, later, by the methodology applied (19 studies were based on comprehensive interventions, 11 focused on the nuclear symptoms of autism spectrum disorder (ASD), 12 focused on the promotion of positive parenting, and nine interactions focused on child play). Once all of the documents had been analyzed, the evidence indicated scientific efficacy in most studies, mainly in those based on child development and the application of behavioral analysis principles. Moreover, the positive influence of parent participation in such programs was demonstrated.